Inactivation of isoprenylcysteine carboxyl methyltransferase reduces proliferation of BRAF and NRAS mutated human melanoma cells - Thorisson, Bjarni (My University, 2011)
Malignt melanoma is the deadliest form of skin cancer, with an increasing incidence worldwide. Surgical removal of the tumors can be an effective first line of defense. Nonetheless, when the tumors have metastasized, the prognosis is extremely poor and not influenced by systematic therapy with cytotoxic drugs. The two most common mutations in malignant melanoma are BRAF and NRAS, with the prevalence of 47% and 21%, respectively. Newly developed selective inhibitors have shown profound clinical results in patients that carry the BRAFV600E mutation. However, the patients develop secondary resistance and subsequent disease progression. Also, tumors caused by mutations of NRAS or other oncogenes are accelerated by the BRAF selective inhibitors. It is therefore of paramount importance to explore alternative or combinatorial therapies to mitigate the incurred resistance mechanism. Isoprenylcysteine carboxyl methyltransferase (ICMT), is an endoplasmic reticulum membrane protein that catalyzes post-translational carboxyl methylation of proteins encoding a C-terminal CAAX motif (C, cystein, A, aliphatic amino acids, X, any amino acid). CAAX proteins have proved important for the function of various cancer cells, and preclinical studies have shown that inactivation of ICMT might be a potential target for anticancer drugs. In this study we evaluated the impact of inactivating ICMT in BRAF and NRAS mutated human melanoma cell lines, alone and in combination with BRAF inactivation and thereby determine if ICMT inactivation or co-inactivation of ICMT and BRAF would reduce the proliferative ability of these cells. By using lentiviruses expressing ICMT- and BRAF- specific short hairpin (sh) RNA, we knocked down expression of ICMT and BRAF independently and in combination in these mutated melanoma cell lines. Inactivation of ICMT or BRAF alone significantly reduced the proliferation of BRAF and NRAS mutated human melanoma cell lines. The simultaneous inactivation of ICMT and BRAF resulted in a significant reduction of proliferation in these cells. However, the reduction did not exceed independent inactivation of ICMT or BRAF. These results indicate that targeting ICMT in human malignant melanoma could be an attractive strategy, which will be further explored.
Keywords: Livsvetenskaper; Industriell bioteknik; Life Science; Industrial Biotechnology